2016
DOI: 10.3389/fpsyg.2016.00218
|View full text |Cite
|
Sign up to set email alerts
|

But I Was So Sure! Metacognitive Judgments Are Less Accurate Given Prospectively than Retrospectively

Abstract: Prospective and retrospective metacognitive judgments have been studied extensively in the field of memory; however, their accuracy has not been systematically compared. Such a comparison is important for studying how metacognitive judgments are formed. Here, we present the results of an experiment aiming to investigate the relation between performance in an anagram task and the accuracy of prospective and retrospective confidence judgments. Participants worked on anagrams and were then asked to respond whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
85
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 55 publications
12
85
2
2
Order By: Relevance
“…Concurrent EEG recordings showed that functional connectivity between prefrontal regions and motor areas increased after a first-order response, specifically when a metacognitive judgment was required. Together with previous findings (Fleming et al 2015;Siedlecka et al 2016;Fleming 2016;Wokke et al 2017), our results demonstrate that post-decisional action information contributes to metacognitive decision-making, thereby painting a picture of metacognition as a second-order process employing endogenous control mechanisms. Verbal confidence ratings were recorded either at the end of each trial (ACT), or directly preceding the first-order response (PRE_ACT), or directly following stimulus presentation (PRE_CUE).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Concurrent EEG recordings showed that functional connectivity between prefrontal regions and motor areas increased after a first-order response, specifically when a metacognitive judgment was required. Together with previous findings (Fleming et al 2015;Siedlecka et al 2016;Fleming 2016;Wokke et al 2017), our results demonstrate that post-decisional action information contributes to metacognitive decision-making, thereby painting a picture of metacognition as a second-order process employing endogenous control mechanisms. Verbal confidence ratings were recorded either at the end of each trial (ACT), or directly preceding the first-order response (PRE_ACT), or directly following stimulus presentation (PRE_CUE).…”
Section: Resultssupporting
confidence: 85%
“…Critically, stimulation of premotor areas reduced metacognitive capacity without changing visual discrimination performance. Further, it has been shown that the order of rating confidence (before or after the response) influenced metacognitive performance on an anagram problem-solving task (Siedlecka et al 2016). From a computational perspective, Pasquali and colleagues explored neural network architectures aimed at capturing the complex relationships between first-order and second-order (metacognitive) performance in a range of different cognitive tasks and suggested that metacognitive judgments are rooted in learned redescriptions of firstorder error information rather than in the relevant first-order information itself (Pasquali et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 6D we replot their data alongside the second-order model simulation at constant stimulus strength (Figure 6E). Siedlecka et al (2016) found that metacognitive sensitivity was greater in the tDM than the tMD conditions, in accordance with the predictions of a second-order model in which actions inform confidence ratings. In addition, confidence was overall lower in the choose-rate case, although unlike the effect on metacognitive sensitivity, this was not statistically significant.…”
Section: Results (1): Features Of Second-order Computationsupporting
confidence: 82%
“…While revising our manuscript for publication (and after developing these simulations) we became aware of a published dataset that directly tested and confirmed our predictions (Figure 6D). Siedlecka et al (2016) asked subjects to provide confidence ratings about whether a target word presented on the screen was the solution to a previously studied anagram. In a between-subjects design, participants were assigned to one of three conditions: deciding if a target word was an anagram and then judging confidence (target-decision-metacognitive judgment, tDM); judging confidence after seeing the target but before making a decision (tMD); or rating confidence before seeing the target word (MtD).…”
Section: Results (1): Features Of Second-order Computationmentioning
confidence: 99%
“…In previous work, vividness ratings were often recorded after the mnemonic decision, meaning that judgments could reflect the participants’ perception of how they had performed on that trial; moreover, vividness and precision or retrieval success effects were not distinguished, such that vividness is likely to have been confounded with precision and/or retrieval success. In the current study, making the vividness rating before any decision on the objects ensured that it reflected participants’ assessment of their subjective ability to bring to mind the appearance of the objects on the display, rather than the influences of perceived difficulty or post-decision processing (Siedlecka et al, 2016). Second, we modeled vividness, retrieval success and precision within the same general linear model, meaning that they accounted for independent sources of variance.…”
Section: Discussionmentioning
confidence: 99%